2010
DOI: 10.1097/jto.0b013e3181f77a6a
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Utility Values from European Organization for Research and Treatment of Cancer Quality of Life-Core 30 Questionnaire Values in Lung Cancer

Abstract: Introduction:Cancer clinical trials frequently incorporate quality of life (QoL) measures but rarely patient utility. Utility information is required for cost utility evaluations of novel cancer therapies. We assessed the feasibility of converting QoL data into utility scores using the European Organization for Research and Treatment of Cancer Quality of Life-Core 30 questionnaire (EORTC QLQ-C30) and the EQ-5D in patients with non-small cell lung cancer (NSCLC). Methods: Outpatients with all different disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 12 publications
1
42
2
Order By: Relevance
“…While responses on the FACT-G were obtained from Canadian cancer patients, the scoring functions of the EQ-5D and SF-6D are based on non-Canadian populations. These tariffs have been demonstrated that they are valid in a Canadian population [50-53]. However, the constructed mapping algorithms from this study may not be transferrable to patients of other countries.…”
Section: Discussionmentioning
confidence: 96%
“…While responses on the FACT-G were obtained from Canadian cancer patients, the scoring functions of the EQ-5D and SF-6D are based on non-Canadian populations. These tariffs have been demonstrated that they are valid in a Canadian population [50-53]. However, the constructed mapping algorithms from this study may not be transferrable to patients of other countries.…”
Section: Discussionmentioning
confidence: 96%
“…Total scores were translated onto a scale from 0 to 100, according to algorithm provided in the WHO QOL–BREF manual. This scale was treated as a preference measure, as it has increasingly been derived for calculating QALY estimates for use in health‐care economic studies . The score differential between t1 and t0 was weighted with the individual days between the two measurements to yield an individual QALY measure for each family member.…”
Section: Methodsmentioning
confidence: 99%
“…Scores from these instruments can be converted to utilities using published transformation algorithms. [8][9][10][11][12][13][14][15][16] While there have been numerous studies of health-related quality of life (HRQOL) in patients with melanoma, [17][18][19][20] most did not express the results as utilities and are therefore difficult to use in cost-effectiveness analyses. Furthermore, some HRQOL studies report more than one mean utility estimate (as in the case where patients complete more than one preference-based measure), which requires correlation between these values to be examined in order to interpret the results.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…time trade‐off, standard gamble), (ii) multiattribute utility measurements, such as the EuroQoL group's EQ‐5D‐5L, or (iii) transformation of data from generic nonutility‐based quality‐of‐life instruments such as the Short Form 36‐item health survey (SF‐36), or disease‐specific instruments such as the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire core 30 (EORTC QLQ‐C30) or the Functional Assessment of Cancer Therapy (general, FACT‐G, and melanoma, FACT‐M). Scores from these instruments can be converted to utilities using published transformation algorithms …”
mentioning
confidence: 99%